SELF ESTEEM AND THE LEVEL OF CONFIDENCE IN STUDENTS - Dita Anggia Putri; M. Jorgie Arroyandy; Chairunissa; Reira Izzatunissa; M. Ihsanudin (CV. Doki Course and Training, 2023)
Self-esteem can be defined as how people feel about themselves in relation to the importance of achievement, positive interpersonal relationships, and psychological well-being (Vohs & Baumeister, 2016). This research is limited, with the aim of knowing the relationship between self esteem and the level of confidence of 4th semester students. The total number of research respondents is N = 40. Data collection was carried out through goggle form with the type of Quantitative research with sequential explanatory design and purposive sampling technique. The results showed that there is a relationship between self esteem and self-confidence of 4th semester students of UIN Raden Fatah Palembang.